Representation and Meaning of Space According to Metaphysical Architecture - Iis Septianingrum; Eny Irmawati; Fairuz Mutia (Architectural Research Journal, 2022)
A space in architecture always has a different representation and meaning, according to what the architect who designed the space of an architecture wanted to convey. Along with the development of the world, architecture has also undergone several changes. These changes require the Architect to follow the demands of the market without considering other elements in the architecture, one of which is the element of metaphysics. Which is one of the important elements in architecture. As stated by Lorens Bagus 1996, "Contemplation in metaphysics is the appreciation of thoughts for thoughts that bring happiness, which is obtained through the actualization of the individual's highest ability, namely reason". And in its changes, architecture begins to lose the representation and meaning of a space that is formed from the architectural process. This limits the space for the architects to represent the meaning of their work. In fact, as we know that the representation and meaning of space is the way the architect communicates with its users indirectly and can restore the architect's image as an expression of himself. In the process of making this journal, we used data collection methods from various sources.